2019
DOI: 10.1111/jop.12828
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic analysis of oral keratinocytes chronically exposed to shisha

Abstract: Background Tobacco is smoked in different form including cigarettes and water pipes. One popular form of water pipe smoking especially in Middle Eastern countries is shisha smoking. Shisha has been associated with various diseases including oral cancer. However, genomic alterations and gene expression changes associated with chronic shisha exposure have not been previously investigated. Objectives Whole‐exome sequencing and gene expression profiling of immortalized human oral keratinocytes (OKF6/TERT1) cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…A recent study by Maitra et al reported a similar observation of higher C>G transversion in gingiva-buccal OSCC patients with a tobacco-chewing history (12). Another study by our group employed whole-exome and RNA-Seq analyses of oral keratinocytes exposed to Shisha tobacco and demonstrated enrichment of Interferon signaling pathway and activation of MAPK1 pathway (13).…”
Section: Introductionsupporting
confidence: 60%
“…A recent study by Maitra et al reported a similar observation of higher C>G transversion in gingiva-buccal OSCC patients with a tobacco-chewing history (12). Another study by our group employed whole-exome and RNA-Seq analyses of oral keratinocytes exposed to Shisha tobacco and demonstrated enrichment of Interferon signaling pathway and activation of MAPK1 pathway (13).…”
Section: Introductionsupporting
confidence: 60%
“…47 The effects of waterpipe smoking on periodontal and oral health have been examined through cross-sectional observations [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] and limited in vitro assays. 70,71 However, the demographics of waterpipe usage limits the majority of human studies to males of Middle Eastern origin. These methodologically limited studies demonstrate lower mean age-adjusted periodontal bone levels, deeper vertical bony defects, deeper periodontal probe depths, lower gingival bleeding, and higher plaque levels in waterpipe users.…”
Section: Waterpipesmentioning
confidence: 99%
“…Waterpipe smoking also increased the risk of developing peri-implantitis. 51,52,54,63,64,69 Microbiologic, immunologic, and histochemical studies have demonstrated a dose-dependent cytotoxic effect 68,70,71,[73][74][75] and mutagenic effect 75 on buccal mucosa, as well as enrichment of specific pathogenic bacteria 76 and Candida albicans 61,67 in waterpipe users.…”
Section: Waterpipesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a series of multiomic studies carried out by our group provided substantial evidence to indicate that chronic exposure to WS leads to oncogenic transformation in normal human oral keratinocytes. [5][6][7][8] The main component used in these studies is 'shisha'-a processed tobacco variant blended with flavors and additives.…”
Section: Introductionmentioning
confidence: 99%